2006
DOI: 10.1143/jjap.45.3988
|View full text |Cite
|
Sign up to set email alerts
|

Straight and Smooth Etching of GaN (1100) Plane by Combination of Reactive Ion Etching and KOH Wet Etching Techniques

Abstract: GaN striped structures along the <11 20 > and <1 100 > directions were fabricated by a combination etching technique, consisting of reactive ion etching followed by KOH wet etching. After wet etching, the sidewalls of the striped structures along the <11 20 > direction became very smooth and straight, compared with normal wet etching and dry etching. From the differences of the etching along the <1 100 > direction, it was found that etching mainly occurs in the (1 100) plane. This phenomenon can be explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 32 publications
2
48
0
1
Order By: Relevance
“…These phenomena did not depend on the KOH concentrations. The etching mechanism can be explained by the actions of hydroxide ions (OH) at the m plane surface [14], similar to the etching mechanism at the -c plane proposed by Li et al [15].…”
Section: Etching Propertiessupporting
confidence: 59%
“…These phenomena did not depend on the KOH concentrations. The etching mechanism can be explained by the actions of hydroxide ions (OH) at the m plane surface [14], similar to the etching mechanism at the -c plane proposed by Li et al [15].…”
Section: Etching Propertiessupporting
confidence: 59%
“…We can also observe in Fig. 5 that the sidewall of the a-plane (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) should only be formed by etching the inclined plane of the a-plane (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) first.…”
Section: Resultsmentioning
confidence: 76%
“…According to Stocker and Schubert's [20] result in 1998, KOH mainly produces {10-1-1}-plane and {10-10}-plane in GaN materials. The etching mechanism of KOH on the GaN has been studied [15,21], and we have observed that different morphology formations are created by different polarities and surface bonds [22,23]. However, these literatures pay less attention to the aspect of etching mechanism and do not have sufficient experimental evidence in support of their conclusions.…”
Section: Introductionmentioning
confidence: 97%
“…Similar results are reported by a number of previous studies on wet chemical etching of GaN using alkaline solution. [25][26][27][28] Etching-rate difference on crystallographic face is qualitatively explained by the difference of dangling bond density (DBD), which is a function of surface energy. 25,26 The DBDs of the (0001) and {1−100} planes are 11.4 and 12.1 nm −2 , respectively, which is smaller than those of the other planes (e.g., {11−20} plane (14.0 nm −2 ) and {1−101} plane (16.0 nm −2 )), indicating that these planes are relatively stable toward wet chemical etching.…”
Section: Resultsmentioning
confidence: 99%